THE RENEWAL OF THE GREEK ILLUSTRATED CHILDREN’S BOOK DURING THE METAPOLITEFSI - Delfino, Ioanna (Design/Arts/Culture, 2023)
With the restoration of democracy in Greece in 1974 a period of transition began, known as metapolitefsi, which saw deep political, social and economic changes. Progressive developments also occurred in art, culture and education. The rules of the new pedagogy affected the field of literature and more specifically children’s illustrated books. Thus, writers departed from the old conservative models, dominated by protectionism and superficial idealism. Instead, they introduced political, social and environmental concerns, while the language became friendlier and modern. At the same time, illustrators such as Kyritsopoulos, Zarampouka, Fakinou, Maroulakis, Psaraki a.s.o., begin to move away from the dry literalness and naive realism of most of their predecessors. They draw on a wide range of sources, from cartoons to abstraction and from Art Nouveau to Pop Art, they experiment with techniques never before used in Greek book illustration, and use innovative symbolism to convey textual meanings. Their style becomes intimate, imaginative and humorous. Pictures are no longer a merely decorative accompaniment to the text which is particularly important. They often cover the entire surface of the page, and play a decisive role in the development of the story. In short, they become central to the experience of the book. It is no coincidence that the young illustrators of the 70s and 80s often wrote their own texts. Typography, too, escapes from strict rules. Handwritten lettering, previously unheard of in Greek books, is often used on covers and title pages. Overall, during the early years of the Greek metapolitefsi, children’s illustrated books changed radically and caught up with international developments. The predictable layout and obvious didacticism of previous decades, especially during the military junta (1967-1974), gave way to sophistication, sensitivity and wit, fresh and intelligent ways of introducing children to real-life social and ethical issues.